Potential Analysis and Mapping of Porang Plants in International Export Markets - Haerunnisa; Fitri Hayati; Ricky Firmansyah (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2023)
Farmers in Indonesia are a mainstay in the development sector, so government programs are one of the factors in the hopes of Indonesian farmers to improve the welfare of farmers, this potential requires optimized management to meet domestic food needs, one of which is the success of farmers planting root crops, especially root crops. Porang, the Iles-iles plant is a tuber-producing plant that can be consumed. This study used the literary study method, collecting data obtained from various sources, including journals, books, documentation, the internet and libraries. According to research results, in 2020, Japan's imports of people reached 29.0% of the world's total imports of people. This makes Japan the second largest importer in the world after the United States, which has an import share of 41.4%.